2006
DOI: 10.1111/j.1464-410x.2006.06126.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidental renal tumours: the frequency of benign lesions and the role of preoperative core biopsy

Abstract: OBJECTIVE To determine the incidence of benign renal lesions in incidentally discovered small renal tumours, increasingly detected by the widespread use of abdominal imaging, and to evaluate whether preoperative renal core biopsy is effective in identifying benign lesions. MATERIALS AND METHODS In a retrospective study, renal core biopsies for incidental tumours over a 5‐year period were analysed. The biopsies were correlated with the final pathology of the nephrectomy specimens, or with patient follow‐up if n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 17 publications
6
72
0
3
Order By: Relevance
“…There were 15 core biopsy studies that used 18G needles. 5,13,15,16,18,20,21,[23][24][25][26][27][28][29][30] Eleven studies included biopsies performed using multiple imaging modalities (primarily CT or ultrasound). Radiation exposure from CT guidance occurred in 44.3%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were 15 core biopsy studies that used 18G needles. 5,13,15,16,18,20,21,[23][24][25][26][27][28][29][30] Eleven studies included biopsies performed using multiple imaging modalities (primarily CT or ultrasound). Radiation exposure from CT guidance occurred in 44.3%.…”
Section: Resultsmentioning
confidence: 99%
“…2). 5,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] One evaluated FNA with cytopathology alone 12 and all other studies evaluated core needle biopsy with surgical pathology. There were 15 core biopsy studies that used 18G needles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vasudevan et al reported a 33% benign histology in 70 renal masses smaller than 5 cm 5 . Similarly, a report of 100 laparoscopic partial nephrectomies for a mean tumour size of 2.9 cm showed that 32% of the surgeries were performed for benign disease, as indicated by the final pathology specimen 6 .…”
Section: Pathologic Featuresmentioning
confidence: 99%